KAJIAN PERUBAHAN PENGGUNAAN LAHAN DAN DAYA DUKUNG BIOEKOLOGI KAWASAN PUNCAK TERHADAP RTRW KABUPATEN BOGOR - , Tika Rachmawati ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The area of research is the Puncak area in Bogor Regency, includes sub Ciawi, Cisarua and Megamendung as a part of the Regions Bogor, Puncak, Cianjur (Bopunjur) and as a catchment and protected area (RTRW of Bogor Regency, period on 2005-2025). Purpose of this study were: (1) assess changes land use during the period 2005-2010 in the area of Puncak, Bogor regency, (2) count the value of existing resources support bioekologi on condition of 2005 and 2010 and 2005-2025 rtrw bogor regency years (3) examine the relationship of land use change on the carrying capacity of the environment and spatial planning bioekologi Bogor period on 2005-2025, and (4) formulate a strategy management of ecological land use at Puncak area. This research is descriptive qualitative and kuantatif, using secondary data analysis. The mathematical analysis of the ecological footprint approach (Global Footprint Network (GFN) and the World Wildlife Fund (WWF)) by calculating the value of ecological footprint, biocapacity and the carrying capacity of bioecology presented spatially. The results of this study are: (1) the total area of land use in the area of the Puncak experience major changes in the period 2005-2010, namely: agricultural land decreased from 7488,82 Ha to 5976,72 Ha forests reduced from 6444,49 Ha to 5158,49, and land up increased from 1925.808 Ha to 4225.987 Ha fields from 3562.050 Ha to 2122.762 Ha, (2) changes in land use greatly affects the impairment of the carrying capacity of bioecology and RTRW of Bogor regency, namely: (a) the value of DDE in 2010 in the study area decreased from the value of DDE in 2005, and (b) the difference in value of the existing DDE to the value of DDE RTRW is negative in almost all areas of research. This indicates that it was too broad land uses incompatible with existing land use plans in Bogor regency spatial planning and RTRW of Bogor Regency Year 2005-2025 is not accommodate the land use plan in the Puncak area. Formulation of strategies management the most appropriate use of land ecology are: (a) reduce the area of land up around the summit region, especially in protected areas and conservation, forest rehabilitation also introduced a system of ecology-based tourism, (b) optimizing spatial planning with spatial planning and control concept of spatial patterns, space utilization and integrated institutional, effective, and enforceable efiaien, and involve the community in monitoring and supervision so that the Puncak of development in the region, Bogor regency sustainable.